Tropical forest biodiversity and the world heritage convention - Sayer, Jeffrey A.; Ishwaran, N.; Thorsell, J.; Sigaty, T. (2000)
The World Heritage Convention has been ratified by 158 countries and provides an international legal regime for the conservation of sites of global, cultural or natural value. There are 33 tropical forest sites listed under the convention, mainly for their global biodiversity value. They constitute an elite set of biodiversity sites covering approximately 2.5% of the world’s closed tropical forests and making a significant contribution to the conservation of the world’s terrestrial biodiversity. A range of international initiatives will eventually provide a framework for better conservation and sustainable management of forests worldwide, but the World Heritage Convention provides an existing mechanism, which could quickly be mobilised to safeguard the most important forests. In the past, sites were selected for listing under the convention if they were perceived to have minimal human impact. However, all forests are modified by humans but that modification need not be inconsistent with the maintenance of global biodiversity values. The Convention could have greater impact if it addressed more directly the reality of the ubiquitous human modification of forests. This could be achieved through use of more adaptive forms of management based on objective criteria and indicators to define tolerance of change and trigger management responses to achieve desired biodiversity outcomes. It is concluded that an optimal list of world heritage tropical forest sites might include up to 100 sites or clusters of sites and that such a network of sites could effectively protect a high proportion of the world’s forest biodiversity. The present rate of attrition of the world’s tropical forests suggests the need for urgent international action to focus on a set of priority sites and the World Heritage Conservation could provide the best international framework for such action.